Forecasting Malaysian Business Cycle Movement:Empirical Evidence from Composite Leading Indicator - Wong, Shirly Siew-Ling; Shazali, Abu Mansor; Puah, Chin Hong; Liew, Venus Khim-Sen (Munich University Library, 2012)
Early detection of a turning point in a business cycle is crucial, as information about the changing phases in business cycles enables policy makers, the business community, and investors to cope better with unexpected events brought about by economic and business situations. The Malaysian economy is fortunate to own a publicly accessible composite of leading indicator (CLI) that is presumed capable of tracing the business cycle movement and thus contributes to the creation of an early signaling tool for short-term economic forecasting.Certainly, the usefulness of this CLI in monitoring the contemporary economic and businesscondition in Malaysia will be empirically appealing to the nation. Even though the presentstudy can display the ability of the Malaysian CLI to trace the business cycle and offers advanced detection of business cycle turning points, the evidence of diminishing lead times foreseen by the CLI significantly weaken the fundamental function of a leading index as an early tool to signal economic vulnerability.